O desempenho escolar de alunos da periferia: elementos para uma etnografia de construção de representações sobre fracasso escolar - Mecena, Elizane Henrique de [UNIFESP] (2011)
This paper aims to comprehend the representants parents, students, teachers and education professionals from a suburb school in a big city have concerning school failure. The chosen approach considered urban researches (VELHO and KUSCHNIR, 2003) because it is believed the school not as an institution apart from the social dynamic as a whole. In order to engage this action, a theoretical-methodological hub was taken for the social configuration study (ELIAS, 2000, LAHIRE, 2004), of the interdependencies and the social relations complexities that may exist in the phenomenon called school failure from suburb students (LAHIRE, 2004). The ethonography (GEERTZ 2008; WOODS 1987,1999 ), together with its researches sources was the prioritized tool to engage an participative research (WHYTE, 2005) which would be able to unravel the representants of the involved groups had in the neighborhood, the school and in possible students profiles (KAPLAN 2009) towards the evaluations from the central state education organ. This organ states to be able to see with this evaluation the development of its schools units as a portrait (picture). Therefore, in the counter-face, the photography (DUBOIS, 1993; ADAMS, 2000; SONTAG 2003, COUTINHO, 2009; SOUTAGE 2010) was also present in this paper making it possible the analysis of an imagery speech which was shown, on the other hand, the site, the people and the school, also supplied conceptual elements where a greater approach was possible as a way to see the school used by the state organ. The use of the tools in the ethonograpical research, as well as the means brought by the camera contributed to make my approach even closer to the people who participated in this research and for me to be absorbed little by little by the community in a duality of belonging and also keeping me as a foreigner in the search to understand the found dynamics. The observations were written down in field notebooks, which were added to the applied structured and semi-structured survey questions contents and from the interviews transcriptions. I have organized groups and searched data in the files and in the school documents. This research was carried out in a suburb school that was evaluated by Saresp (Evaluation System of School Performance in São Paulo) as one the 100th worst schools from the state of São Paulo in performance in 2007. The study subjects were the groups from the morning and afternoon shifts from the 5th grade from elementary school until the 3rd year of high school , teachers, parents, students, and school professionals who participated in the research and made the analysis possible. The overall situation was analyzed according to BAUMAN (2003,2005,2008,2009); LAHIRE (2004); DUBET (2008). The analysis showed that who make the everyday school know the difficulties found in order to achieve school success, showed their feelings, their conflicts inside and outside the school to overcome the school failure.